Adesivos multi-uso-avaliação da resistência adesiva a dentina frente a teste de cisalhamento, estereomicroscopia e microscopia eletrônica de varredura - Gonçalves, Sérgio Eduardo de Paiva [UNESP] (Universidade Estadual Paulista (Unesp), 1994)
Recent bonding systems have been advocated as multi-purpose bonding agents. The aim of this study was to determine if some of these bonding systems could be associated to composite resins from different manufacturers. This investigation was conducted to test lhe shear bond strength of three bonding systems: Scotchbond Multi-Purpose (3M Dental Products), Optibond Light Cure (Kerr) and Optibond Dual Cure (Kerr), when each of them was associated to lhe composite resins: Z1 00 (3M Dental Products), Prisma - APH (Dentsply) and Herculite XRV (Kerr). Seventy-two flat dentin bonding sites were prepared to 600 grit on human premolars mounted using acrilic resins. The teeth were assigned at random to 9 groups of 8 samples each. A split die with a 3mm diameter was placed over lhe surface of lhe dentin treated with one of lhe adhesive systems, and lhe selected composite resin was inserted and light cured. The split mold was removed and all samples were termocycled and stored in 37ºC water for 24 hours before testing. Shear bond strength was determined using an lnstron Universal testing machine. Some failures were examined under lhe S.E.M. Data was analysed by one-way analysis of variance, that demonstrated a significant difference (p<0,05) in the mean shear bond strength among Optibond Light Cure (15,446 MPa), Scotchbond Multi-Purpose (13,339 MPa) and Optibond Dual Cure (10,019 MPa). These values did not depend on the composite resin used. The association between bonding system/composite resin was statistycally significant (p<0,05) and the best results were obtained when the composite resins Z100 and Herculite were used with the adhesive system Optibond Light Cure, and when the composite resin APH was used with the adhesive system Scotchbond Multi-Purpose

Adesão tem sido a meta das pesquisas Odontológicas nas últimas décadas. Para determinar se os mais recentes sistemas adesivos denominados como MULTI-USO poderiam ser utilizados associados a diferentes marcas comerciais de resina composta, em dentina, foram realizados testes de resistência ao cisalhamento. Setenta e dois corpos de prova foram confeccionados utilizando-se dentes pré-molares humanos íntegros, embutidos em resina acrílica, expondo-se a dentina por tratamento com lixas d'água de granulações 180, 400 e 600. Os corpos de prova foram divididos em três grupos: Grupo 1 Scotchbond Multi-Purpose (3M), grupo 2 - Optibond Light Cure (Kerr) e grupo 3 - Optibond Dual Cure (Kerr). Todos os grupos foram subdivididos em sub-grupos de 8 dentes, nos quais foram inseridas as resinas compostas: a-Z1 00 (3M do Brasil), bPrisma APH (Dentsply) e c- Herculite XRV(Kerr). Os corpos de prova foram submetidos à ciclagem térmica e após 24 horas de armazenamento em água destilada 370C, aos testes de resistência ao cisalhamento em máquina lnstron 4301 seguidos de análise em estereomicroscópio Technivai-Carl Zeiss de aumento para avaliar o tipo de fratura e, análise em microscopia eletrônica de varredura (M.E.V.). A aplicação do modelo estatístico de análise de variância permitiu a constatação de que o fator Adesivo apresentou um valor significante (p<0,05) independente do fator Resina, tendo o adesivo Optibond Light Cure propiciado a maior resistência média ao cisalhamento (15,446 MPa), seguido do Scotchbond Multi-Purpose (13,340 MPa) e do Optibond Dual Cure (1 0,019 MPa). A interaçâo Adesivo x Resina apresentou um valor estatisticamente significante (p<0,05), onde os melhores resultados foram obtidos entre as resinas Z100 e Herculite XRV com o adesivo Optibond Light Cure, e entre a Resina APH com o adesivo Scotchbond Multi-Purpose. Concluímos que o adesivo Optibond...
Keywords: Adesivos dentarios; Cavidade da polpa dentaria; Materiais dentários; Dentina; Dental materials